Noor eaudiobook - Okorafor, Nnedi (Tantor Media, 2021)
From Africanfuturist luminary Okorafor comes a new science fiction novel of intense action and thoughtful rumination on biotechnology, destiny, and humanity in a near-future Nigeria. Anwuli Okwudili prefers to be called AO. To her, these initials have always stood for Artificial Organism. AO has never really felt . . . natural, and that's putting it lightly. Her parents spent most of the days before she was born praying for her peaceful passing because even in-utero she was "wrong." But she lived. Then came the car accident years later that disabled her even further. Yet instead of viewing her strange body the way the world views it, as freakish, unnatural, even the work of the devil, AO embraces all that she is: A woman with a ton of major and necessary body augmentations. And then one day she goes to her local market and everything goes wrong. Once on the run, she meets a Fulani herdsman named DNA and the race against time across the deserts of Northern Nigeria begins. In a world where all things are streamed, everyone is watching the "reckoning of the murderess and the terrorist" and the "saga of the wicked woman and mad man" unfold. This fast-paced, relentless journey of tribe, destiny, body, and the wonderland of technology revels in the fact that the future sometimes isn't so predictable. Expect the unaccepted.